Cataract Surgery in Fuch’s Corneal Dystrophy - Shikha Gupta; Varun Gogia; Ritika Sachdev; Rajesh Sinha; Namrata Sharma (Delhi Journal of Ophthalmology)
Fuch’s endothelial corneal dystrophy is a progressive disorder of the endothelium wherein a gradual decline of functional endothelial cells over the years, manifesting with visual disturbance in late adulthood. The visual loss in these patients can be either due to cataract or due to corneal dystrophy itself. Determining which patient requires cataract surgery is imperative for an ophthalmologist to visually rehabilitate the patient. However cataract surgery could potentially decompensate an already diseased cornea with borderline endothelial cell reserve. This review will help the surgeons in proper evaluation and practice during surgery to provide the patient with maximal visual gain.